Occurrence and Distribution Patterns of Magnetic Particles Within Stalagmite Growth Laminae. (22nd September 2022) - Shi, Taiheng; Ding, Jianyv; Zhu, Zongmin; Zhang, Hongbin; Huang, Junhua
Abstract: The concentrations of magnetic particles in stalagmites depend greatly on the regional hydrologic condition, and thus can act as an important proxy for paleoclimate reconstruction. The central axis region of a stalagmite is usually selected for such magnetism study. However, little is known about the distribution and influence factors of exogenetic magnetic particles within the growth laminae. In this study, the occurrence and variations of magnetic particles along the growth laminae of three shape stalagmites were investigated by a set of magnetic measurements, including isothermal remanent magnetization (IRM) acquisition curves and low‐temperature magnetic analysis. The results show the main magnetic remanence carrier is detrital magnetite/maghemite, coexisting with small amounts of hematite and goethite. The distribution of soft magnetic particles along the growth laminae showed different patterns among the three shape stalagmites (dome, cone, and candle). For the dome shape stalagmite, the soft magnetic particle concentrations in all studied growth layers showed an increasing trend from center to edge. Similar patterns were also appeared in the bottom growth layers of the cone and candle shape stalagmites. This edge enrichment of magnetic particles is caused by drip water washing effect. However, such enrichment pattern became weaker or even inverse in the top growth layers of the cone and candle shape stalagmites, indicating that the shapes of stalagmites could also affect the surface distribution of soft magnetic minerals. These uneven distributions of magnetic particles imply that the central axis region of a stalagmite may not always be the optimal specimen for environmental magnetism study. Key Points: Detrital magnetic particles are unevenly distributed within growth laminae and affected by stalagmite shapes and drip water washing effect The central axis region of a stalagmite may not always be the optimal specimen for environmental magnetism study